(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The energy stored Quasi-Z-source Inverter (qZSI) allows integrate energy storage in addition to the other energy source mainly for output power smoothening. Single phase inverter suffers from double-frequency power ripple in the input side and also in the energy storage that is transferred there from the ac-side. In qZSI must be used large electrolytic dc capacitors in the impedance network to suppress this 100 Hz ripple. Also to suppress this ripple can be applied two types of power decoupling: passive power decoupling and active power decoupling. In this paper is analyzed passive power decoupling that is realized by means of the modified control strategy that produces the time-varying shoot-though duty cycle to mitigate power ripple without deteriorating of the output power quality. The validity of proposed control strategy was confirmed by simulation results that were obtained in PSIM software.